The singularity of Raymond Kurzweil as a vision of history - Szymański, Kamil (Hybris, 2019)
In my article I present the characterization of the state of "singularity" as an upcoming moment in history, which is being foretold by Raymond Kurzweil – futurologist, computer scientist and transhumanist. I also present the concept of dividing history into six epochs proposed by Kurzweil, who captures the history of the whole universe as a process of increasing the amount of information. In describing Kurzweil's thought, I do it from the philosophical point of view, showing its historiosophical moments.